Atmospheric structure and dynamics as the cause of ultraviolet markings in the clouds of Venus. - Titov, D; Taylor, F; Svedhem, H; Ignatiev, N; Markiewicz, W; Piccioni, G; Drossart, P (Nature Publishing Group, 2008)
When seen in ultraviolet light, Venus has contrast features that arise from the non-uniform distribution of unknown absorbers within the sulphuric acid clouds and seem to trace dynamical activity in the middle atmosphere. It has long been unclear whether the global pattern arises from differences in cloud top altitude (which was earlier estimated to be 66–72 km), compositional variations or temperature contrasts. Here we report multi-wavelength imaging that reveals that the dark low latitudes are dominated by convective mixing which brings the ultraviolet absorbers up from depth. The bright and uniform mid-latitude clouds reside in the 'cold collar', an annulus of cold air characterized by approx30 K lower temperatures with a positive lapse rate, which suppresses vertical mixing and cuts off the supply of ultraviolet absorbers from below. In low and middle latitudes, the visible cloud top is located at a remarkably constant altitude of 72 ± 1 km in both the ultraviolet dark and bright regions, indicating that the brightness variations result from compositional differences caused by the colder environment rather than by elevation changes. The cloud top descends to ~64 km in the eye of the hemispheric vortex, which appears as a depression in the upper cloud deck. The ultraviolet dark circular streaks enclose the vortex eye and are dynamically connected to it.